2014
DOI: 10.1117/1.jbo.19.4.046022
|View full text |Cite
|
Sign up to set email alerts
|

Accurate single-shot quantitative phase imaging of biological specimens with telecentric digital holographic microscopy

Abstract: Abstract. The advantages of using a telecentric imaging system in digital holographic microscopy (DHM) to study biological specimens are highlighted. To this end, the performances of nontelecentric DHM and telecentric DHM are evaluated from the quantitative phase imaging (QPI) point of view. The evaluated stability of the microscope allows single-shot QPI in DHM by using telecentric imaging systems. Quantitative phase maps of a section of the head of the drosophila melanogaster fly and of red blood cells are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 45 publications
0
54
0
1
Order By: Relevance
“…The distance d, however, is a relevant parameter in performance of DHM, as shown recently [33,34]. In Eq.…”
Section: Fundamental Of Off-axis Dhmmentioning
confidence: 98%
See 1 more Smart Citation
“…The distance d, however, is a relevant parameter in performance of DHM, as shown recently [33,34]. In Eq.…”
Section: Fundamental Of Off-axis Dhmmentioning
confidence: 98%
“…As direct consequence of this phase term, the DHM becomes a shift-variant imaging system [22,33,34], with important ruining effects in the QPIs.…”
Section: Fundamental Of Off-axis Dhmmentioning
confidence: 99%
“…28,30 Multicellular organisms have been previously studied using optical techniques, but have been limited to studying the superficial structure and motion of the organism due to limited resolution, or have required physical sectioning of the sample for improved resolution of smaller structures. [31][32][33][34] We propose using QPI as a label-free method for studying the arthropod external morphology and subcuticular structures. In this study, using both SLIM and the Hamamatsu Nanozoomer, we imaged a whole unstained springtail (Arthropod, Collembola) Ceratophysella denticulata mounted on a slide.…”
Section: Introductionmentioning
confidence: 99%
“…However, our research group has recently demonstrated that the optical capture stage controls the accuracy of QPI-DHM. [5][6][7] Specifically, we showed that QPI-DHM operating in telecentric mode-producing a 2D image of a 3D object-provides very accurate diffraction-limited quantitative phase images with minimal post-processing. This accuracy can be very useful for the diagnosis of different diseases and for specimen identification.…”
mentioning
confidence: 99%